THE DIALECT STATUS OF MADURESE GEOGRAPHICAL DIALECT IN PROBOLINGGO-BONDOWOSO-BANYUWANGI - Lailatu Rochma; Sri Andayani (Program Studi Bahasa Inggris, Universitas Panca Marga, 2023)
Madurese is a language used by the Madura ethnic in their daily communication. This research aim to describe the Madura dialect used in Probolinggo-Bondowoso-Banyuwangi whether the dialect is the same or different, and aims to determine the lexical differences of the Madura dialect in the three research areas and determine the status of the Madura dialect in Probolinggo-Bondowoso-Banyuwangi. This research uses a theory related to dialectology research and uses a quantitative descriptive method using 829 gloss from Swadesh Morrish developed by Nothover and was modified by Kisyani Savitri and also uses purposive sampling method in determining the research area and uses the interview method to collected data. After completing the data, there are 175 gloss of lexical differences was found by using dialectometry method. The result are: Probolinggo-Bondowoso has totally 107 gloss of lexical differences with 61,14% different dialect. Probolinggo-Banyuwangi has totally 162 gloss of lexical differences with 92,57% different dialect. Bondowoso-Banyuwangi has totally 143 gloss of lexical differences with 81,71% different dialect, and the status of the three research areas are different dialect.